The antioxidant effect of Rosa Rugosa - (:unkn) unknown (Freund Publishing House Ltd, 2008)
We examined the effects of Rosa rugosa (Rosa rugosa Thunb) on lipid peroxidation, alanine transaminase (ALT), aspartate transaminase (AST), glutathione and protein oxidation levels in carbon tetrachloride (CCl4) treated male Wistar rats. Two control groups and one treatment group of rats were formed. The control groups were fed a standard diet, while the Rosa rugosa group was fed a standard diet enriched with 6% by weight dried Rosa rugosa fruit powder. After 3 months, a single dose of CCl4 was injected intraperitoneally in the Control II and Rosa rugosa groups (1 ml/kg, as 20% in olive oil) and a similar dose of olive oil was administered i.p. to rats in the Control I group. The rats were sacrificed 2 hours later. Lipid peroxide levels in liver, protein oxidation in liver, glutathione (GSH) levels in liver, and ALT and AST in plasma were measured. The rats in the Rosa rugosa group were found to have significantly lower liver peroxide, protein oxidation, glutathione levels and plasma ALT and AST activities compared with the rats in the CCl4 treated control group. These findings suggest that Rosa rugosa possesses antioxidant activity. © Freund Publishing House Ltd., 2008.
Keywords: ALT; AST; Glutathione; Lipid peroxidation; Protein oxidation; Rosa rugosa